Development of Metacognitive Knowledge of Reading Strategies and Attitudes Toward Reading in Early Adolescence: The Effect on Reading Comprehension - Svjetlana Kolić-Vehovec; Barbara Rončević Zubković; Rosanda Pahljina-Reinić (Psychological Topics, 2014)
The aim of the present study was to examine developmental changes in metacognitive knowledge of reading strategies and attitudes toward reading during early adolescence (from 10 to 14 years), taking gender into account. A secondary aim was also to test a model of the relationships among gender, attitudes toward reading, metacognitive knowledge of reading strategies, and reading comprehension. The sample for this longitudinal study consisted of 175 students. The first data collection took place when the students were enrolled in grade 4 (10 years old), and the follow-up measurements were conducted in grades 6 and 8. At each measurement point, measures of metacognitive knowledge of reading strategies and attitudes toward reading were applied in addition to text comprehension tasks. The obtained results indicated that metacognitive knowledge of reading strategies continuously improved during early adolescence, while attitudes toward recreational reading showed continuous decline from the fourth to the eighth grade, and attitudes toward academic reading dropped significantly between sixth and eighth grades. Girls consistently demonstrated better metacognitive knowledge, as well as more positive attitudes toward both recreational and academic reading when compared to boys. The model that included only attitudes toward recreational reading fitted the data better than the model comprising both academic and recreational reading attitudes. The findings of the path analysis indicated that gender had an effect on recreational reading attitudes that consistently predicted text comprehension directly and indirectly through metacognitive knowledge during early adolescence. The model fitted the data better as students got older.